Pioneer of Medical Missionary Work in China by the Southern Methodist Church:Walter Russell Lambuth - XU Yimeng (Journal of Research for Christianity in China (JRCC), 2025)
Walter Russell Lambuth (1854-1921) often stated that his mission in China was to bring the Gospel of Christ and advanced Western medicine to the Chinese people. Born in China, he held profound affection for the country. Even after his death in Japan, his remains were transported back to China and interred in Shanghai. On this land, he poured all his love and dedication into securing spiritual salvation and physical healing for the Chinese people. To effectively carry out his medical missionary work, Lambuth actively established hospitals and medical programs, cultivating medical professionals for Chinese society. He also ventured deep into impoverished rural areas, treating the sick and preaching the gospel to destitute farmers. Lambuth’s personal charisma and spirit of complete devotion deeply moved the Chinese people, leading many to embrace Christianity as a result.